Learning and collaboration in pre-service teacher education: Narrative analysis in a service learning experience at Andalusian public schools. - Márquez-García, María Jesús; Kirsch, William; Leite-Méndez, Analía Elizabeth (Sciencedirect, 2020)
In this article we take up the task of presenting and analyzing a Service Learning experience developed in a class of the major in Primary Education Teaching at the University of Malaga, in Andalusia, Spain. It consists of a narrative analysis of autobiographical texts –final reports and online interviews – produced by pre-service teachers. We aimed to understand how participants learned about the teaching profession throughout their trajectory in the project. The results indicate pre-service teachers (1) learn by feeling, (2) learn by belonging, (3) learn by placing action in a social perspective, and (4) learn by sharing experiences with others. Keywords: Teacher education; Service learning; Narrative analysis
Se adjunta la versión final aceptada.
Keywords: Profesores - Formación profesional - Andalucía; Teacher education; Service learning; Narrative analysis